Analisis Mekanisme Investasi Emas Melalui Produk Tabungan Emas pada PT. Pegadaian Syariah Cab AR.Hakim Medan - Rizqia Noni Noviantry; Siti Kadariah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to analyze the gold investment mechanism through gold savings products at PT. Sharia Pawnshop Cab AR. Medan Judge and To determine the suitability of the gold investment mechanism through gold savings products, the mechanism is in accordance with MUI Fatwa No. 77/DSN-MUI/V/2010 or not.This research uses descriptive qualitative methods, with data collection techniques through in-depth interviews with employees and Nadabah PT. Sharia Pawnshop Cab AR. Medan Judge as well as observations, documentation and literature studies. The research results show that the gold investment mechanism in gold savings products has been running well, providing easy access for customers, and is assessed in accordance with sharia principles, namely DSN-MUI Fatwa No.77/V/2010 with a combination of wadiah (deposit) and murabahah (sale) contracts. buy) which provides flexibility and certainty for customers in managing gold savings. However, in the mechanism, various challenges arise. Such as customer understanding of the benefits and mechanisms as well as compliance with sharia principles (National Sharia Council Fatwa). The benefit of this research is to provide clear information to customers (the public) regarding the benefits and mechanisms of investing in gold through gold savings, so that it can serve as a guide in making investment decisions. Apart from that, the results of this research can be input for PT. Pegadaian Syariah always provides outreach and education to customers regarding the benefits and mechanisms as well as compliance with sharia. For the University, it can provide useful input and provide references in the field of sharia investment, especially regarding gold savings. This research concludes that gold investment through gold savings products at PT. Sharia pawnshops are a safe and sharia-compliant investment alternative, and have the potential to increase financial inclusion in Indonesia